The performance among foreign workers: a study on CNLT (Far East) Berhad / Ahmad Khusaibe Abu Bakar - Abu Bakar, Ahmad Khusaibe (Faculty of Business and Management, 2007)
Many studies on performance of workers have been conducted, but not many studies focused on the foreign employees performance in organization especially in term of factors that has influenced the foreign employee performance. Thus, purpose this study is to identify the factors regarding to the performance of foreign employees. This study was conducted in CNLT (Far East) Bhd., one the manufacturing company located in Seremban, Negeri Sembilan. In addition, the study done based on foreign employees monthly data from year 2001 to 2005.Besides, these foreign workers data were classified according their origin country. The finding of these study found that all of foreign workers practiced the factors influenced their performance namely absenteeism, annual leave, medical leave and overtime. The result reveals the existence a positive relationship between those factors and performance, but it given significant impact to only workers from three countries. Hopefully, this study can give a lot of benefit to the company, for them to make any decision to improve not only foreign workers but all of the employees worked with company.